Study the Consumer Buying Behavior of Passenger Car Segment in India: Understanding the Consumer Market and Satisfaction in India's Passenger Car Segment (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Automobile industry is India is growing at a brisk pace across the globe and the growth is consistent every year. With many banks providing automobile loans, and increase in the salaries and having huge buying capacity for the middle class people, there are many cars that are hitting the roads. This paper would present about the buying behavior of consumers in the car segments in India. The market is characterized based on the market of the consumers where there would be marketers and manufacturers who would be taken into consideration for consumer orientation and make them satisfied, but would go an extra mile to make the customers happy.